Hubungan Pengetahuan Orang Tua dengan Pelaksanaan Stimulasi Sensori terhadap Perkembangan Anak di TK Islam Baiturrahim - Wanti Hasmar; Indah Permata Sari; Mawaddah Warahmah (Jurnal Akademika Baiturrahim Jambi, 2022)
Early childhood development is the basis of the learning process that will shape experiences and determine the developments that children will carry for life. As an initial foundation, early childhood determines the readiness and success of children in learning in education in the future. The type of research used in this research is quantitative research, namely research in which the data is in the form of numbers or qualitative data that is numbered. The design of this research is correlation with the aim of finding whether or not there is a relationship between parental knowledge and the implementation of sensory stimulation on early childhood development in Baiturrahim Islamic Kindergarten, Jambi. the level of knowledge of parents about the implementation of sensory stimulation on child development at Baiturrahim Islamic Kindergarten Jambi, most of the respondents were in the good category. The implementation of sensory stimulation on child development in Baiturrahim Islamic Kindergarten Jambi, most of the respondents were included in the category of "According" to the implementation of child development according to the stage of development. There is a relationship between the level of knowledge of parents about the implementation of sensory stimulation on child development in Baiturrahim Islamic Kindergarten Jambi.